Feed efficiency in the beef industry - Hill, Rodney A.; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
Feed Efficiency in the Beef Industry provides a thorough and concise overview of feed efficiency in beef cattle. & nbsp; It frames the great importance of feed efficiency to the industry and details the latest findings of the many scientific disciplines that intersect and aim to improve efficient and sustainable production of nutritious beef. The vast majority of production costs are directly tied to feed. With increased demand for grains to feed a rapidly increasing world population and to supply a new demand for alternative fuels, feed costs continue to increase. In recent years, the negative.
The Low-RFI Steer in the FeedlotSteer Carcass and Meat Quality; The Low-RFI Cow; Maternal Productivity; Lessons Learnt on Measurement of Feed Intake and Efficiency; Industry Implementation and Test Standards; Conclusion; References; 6 Nutrition and Feed Efficiency of Beef Cattle; Introduction; Intake and Feed Efficiency Ranges within Beef Cattle; Balancing Postruminal Amino Acid Flow with Consumed Energy; Energy Requirement for Growth; Postruminal Amino Acid Supply; Rumen-Degradable Protein Supply; Impact of Formulating Diets for AA:EE and RDP on Feed Conversion Ratio.
Residual Feed Intake Phenotype Influences Nutritional Requirements.
Print version record.
Keywords: Cattle -- Feed utilization efficiency; Cattle -- Feeding and feeds; Beef industry; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Beef industry; Cattle -- Feed utilization efficiency; Cattle -- Feeding and feeds; Electronic books